Pengaruh Sikap Terhadap Celebrity Endorser Dan Daya Tarik Celebrity Endorser Terhadap Minat Beli Hand And Body Lotion Nivea Di Kota Semarang - Sari, Resly Indah; Idris, Idris (Faculty of Economics and Business | Universitas Diponegoro, 2024)
Current marketing strategies are growing and applied by various companies are marketing strategies that utilize the popularity of a celebrity. This has an effect on consumer purchase intention when buying a product as a result of effective advertising. Consumer attitudes on celebrity endorser become connecting and submission information to other consumers related to the effectiveness of celebrity endorsers. The purpose of this research is to determine the model, hypothesis, indicator, and determine the effect of attitude on celebrity endorser and attractiveness celebrity endorser to purchase intention with brand image as intervening variables on hand and body lotion Nivea consumers in Semarang City. The acquisition of data was taken from 150 respondents selected by purposive sampling method.The population chosen in this research is the user hand and body lotion nivea products domiciled in Semarang City. The consumer criterion is at least seventeen years old and has used a handy and body product at least one time usage. The data were analyzed quantitatively and structurally by applying Structural Equation Modeling (SEM) and using Analysis Moment of Structural (AMOS) version 24 as the analysis tool. The results of the analysis showed that attitude of celebrity endorser positively and significantly on brand image and purchase intention, attractiveness celebrity endorser also has positive and significant on brand image and purchase intention, and the brand image is considered to have a positive and significant on consumers purchase intention on Nivea hand and body lotion. Keywords: attitude toward the celebrity endorser, attractiveness celebrity endorser, brand image, purchase intention